Financial Performance Analysis Based on Financial Ratios at PT Wilmar Cahaya Indonesia Tbk. - Sabda Dian Nurani Siahaan; Gilang Pratama; Ikhsan Maulana; Muhammad Iqbal; Fuji Mori Sirait (Asian Journal of Applied Business and Management, 2023)
This study aims to determine the financial performance of PT Wilmar Cahaya Indonesia Tbk, which is contained in the financial statements on the official website of PT Wilmar Cahaya Indonesia Tbk. This research uses a quantitative descriptive approach using liquidity, solvency, activity, and profitability ratios. The results of the research conducted showed that the financial performance of PT Wilmar Cahaya Indonesia Tbk in 2019–2021 was quite good because the company's liquidity, solvency, activity, and profitability ratios were in good condition.